Institutional repositories in university libraries in Nigeria and the challenge of copyright (2017)
Copyright is a focal issue contending with the development of institutional repositories (IRs). Extant literature focused on the awareness, benefits and the various IR activities across the globe. This study investigated the issues of copyright in institutional repository in universities’ libraries in Nigeria. The study adopted the descriptive survey research design. A multistage sampling procedure was employed to sample 844 lecturers of the universities in Nigeria. Data generated were analyzed using descriptive statistics. The findings revealed that plagiarism, piracy, counterfeiting, photocopying and lack of non workable policy guiding copyright matters and its implementations are among the copy right issues hindering the deployment and sustenance of institutional repositories in Nigeria. The study advocated for adequate legal framework and a workable policy guiding copyright matters.